2020
DOI: 10.1111/ffe.13398
|View full text |Cite
|
Sign up to set email alerts
|

KIcandKIIcmeasurement for hot mix asphalt mixtures at low temperature: Experimental and theoretical study using the semicircular bend specimen with different thicknesses

Abstract: Pure mode I and mode II fracture toughness of asphalt mixture was investigated both experimentally and theoretically using vertical edge crack semicircular bend (SCB) specimen with symmetric and asymmetric bottom loading spans. The thickness of SCB specimen was considered in the range from 30 to 70 mm, and the fracture toughness tests were performed at three subzero temperatures (−5 C, −15 C and −25 C). The results showed that K Ic and K IIc are increased by reducing the test temperature. The thickness had no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 76 publications
(137 reference statements)
1
11
0
Order By: Relevance
“…Nowadays, several specimens with disc‐shaped geometries (with various loading setups) are used to investigate the fracture behavior of geomaterials subjected to pure mode I and pure mode II 28–30 . Some of these specimens are Brazilian disc (BD) specimen, 31–33 flattened BD specimen, 34 center cracked ring‐shaped specimen, 35,36 which are loaded using diametral compression, and the edge‐cracked semicircular bend disc (SCB), 22,37–40 edge‐cracked cylindrical specimen, 41 and edge‐notched disc bend (ENDB), 42–45 which are tested under three‐point bending load. However, specific difficulties can be seen in practice based on the utilized test specimens (e.g., preparation of center or chevron notches in the BD specimens).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, several specimens with disc‐shaped geometries (with various loading setups) are used to investigate the fracture behavior of geomaterials subjected to pure mode I and pure mode II 28–30 . Some of these specimens are Brazilian disc (BD) specimen, 31–33 flattened BD specimen, 34 center cracked ring‐shaped specimen, 35,36 which are loaded using diametral compression, and the edge‐cracked semicircular bend disc (SCB), 22,37–40 edge‐cracked cylindrical specimen, 41 and edge‐notched disc bend (ENDB), 42–45 which are tested under three‐point bending load. However, specific difficulties can be seen in practice based on the utilized test specimens (e.g., preparation of center or chevron notches in the BD specimens).…”
Section: Introductionmentioning
confidence: 99%
“…Review of literature reveals that there are many limited test results for K IIc value of asphalt mixtures and almost all of them have been obtained by testing fixed test geometry (i.e., asymmetric SCB specimen). [53][54][55][56][57][58] On the other hand and according to the literature, despite K Ic value, mode II fracture toughness of brittle materials may depend significantly on the geometry and loading type of the test sample. For example, Aliha and Ayatollahi 59 and Aliha et al 60 showed that mode II fracture toughness of brittle polymeric material (Plexiglas) may vary significantly (from 0.5 K Ic to 1.4 K Ic ) when the test specimen used for K IIc testing is varied.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several researchers have used different laboratory tests including the semicircular bending (SCB) test, 20–28 the dissipated creep strain energy (DCSE) test, 29 the disc‐shaped compact tension (DCT) test, 30,31 the edge notch disc bend (ENDB) test, 32–39 and so on 40,41 for investigating and analyzing the fracture behavior of asphalt mixtures. However, many of these laboratory tests cannot simulate exactly the cracking mechanism of real asphalt mixture in the field 23,36,42–53 . On the other hand, employment of laboratory samples in the real scale of pavement layers and subjected to actual traffic loading is impossible or at least is a very expensive and time‐consuming process.…”
Section: Introductionmentioning
confidence: 99%
“…However, many of these laboratory tests cannot simulate exactly the cracking mechanism of real asphalt mixture in the field. 23,36,[42][43][44][45][46][47][48][49][50][51][52][53] On the other hand, employment of laboratory samples in the real scale of pavement layers and subjected to actual traffic loading is impossible or at least is a very expensive and time-consuming process. Therefore, utilizing numerical analyses can be used as a suitable method to study the fracture behavior of the cracked asphalt pavement.…”
Section: Introductionmentioning
confidence: 99%